Morning serum cortisol as a predictor of synacthen stimulation test outcomes during corticosteroid withdrawal: a comparative analysis of high-dose and low-dose protocols - Saiegh, Leonard; Dakwar, Balsam; Jovanovic, Katya; Rosenblat, Ilana; Mahamed, Muaweya; Sheikh Ahmad, Mohammad (Frontiers in Endocrinology, 2025)
BackgroundProlonged corticosteroid therapy may result in hypothalamic-pituitary-adrenal (HPA) axis suppression and subsequent adrenal insufficiency (AI). The short Synacthen stimulation test (SST) remains the gold standard for assessing adrenal function, yet morning serum cortisol (MSC) may serve as a valuable screening tool during corticosteroid withdrawal.ObjectiveTo evaluate the diagnostic performance of MSC in predicting SST outcomes during glucocorticoid withdrawal and to compare the results of high-dose (HDT) versus low-dose (LDT) Synacthen stimulation protocols. Methods: This retrospective analysis examined 164 SSTs performed between 2006-2021 in patients undergoing prednisone withdrawal assessment. LDT (1 µg Synacthen) was utilized from 2006-2010, followed by HDT (250 µg Synacthen) from 2010-2021. Receiver operating characteristic (ROC) analysis was employed to determine optimal MSC thresholds for predicting adequate adrenal response, defined as cortisol ≥18 µg/dL (500 nmol/L) at 30 minutes.ResultsNo significant differences were observed between LDT and HDT protocols regarding stimulated cortisol levels or test outcomes. ROC analysis revealed optimal MSC thresholds of 10.4 µg/dL (287 nmol/L) for LDT and 11.2 µg/dL (309 nmol/L) for HDT. In the entire cohort, MSC threshold of 10.9 µg/dL (301 nmol/L) demonstrated balanced sensitivity (70%) and specificity (85.5%). Notably, among patients with MSC levels between 10-15 µg/dL (276-414 nmol/L), and 10-12 µg/dL (276-331 nmol/L), 40% and 48% failed the SST, respectively.ConclusionsNo significant differences were observed between LDT and HDT protocols regarding stimulated cortisol levels or test outcomes, and MSC provides valuable adjunctive information for assessing HPA axis recovery. However, a substantial proportion of patients with MSC near the recommended discontinuation threshold of 10 µg/dL (300 nmol/L) still demonstrate abnormal SST responses.